The first reported medieval judicial autopsy on Azzolino Degli Onesti: poisoning or Budd-Chiari syndrome? - Papi, Luigi (Medicina Historica, 2022)
The practice of autopsy on human corpses performed to increase anatomical and physio-pathological knowledge has been reported since ancient times, even if it has often been opposed by medical theories and religious beliefs. The first officially autopsy reported in Italy was that described by Salimbene on 1286 during an epidemy that involved hens and human beings.The development of medico-legal practice on cadavers dates back to the Middle Age in Bologna, the city that boasted the most advanced medical and legal faculties of that period. Some of these autopsy reports have come down to our times and provide interesting information on the medico-legal procedures of that period.In particular, it is illustrated the case of Azzolino degli Onesti: his death was suspected for poisoning but the interpretation of the autopsy report based on current medical knowledge may suggest different conclusions.